Evaluation and Reduction of Energy Consumption of Railway Train Movement on a Straight Track Section with Reduced Freight Wagon Mass - Maryna Bulakh (Energies)
This paper presents an evaluation and reduction of energy consumption during railway train movement on a straight track section with reduced freight wagon mass. A theoretical model was developed to simulate energy consumption based on input parameters, including train speed, track gradient, section length, travel time, and train mass. The results indicate that energy consumption increases by 18.9% as speed rises to 90 km/h and as gradients increase to 2.0‰, while energy consumption decreases by 14.5% on a descending gradient of 1.5‰, which corresponds to the expected dynamics of railway trains. These results are supported by experiments showing that the MAPE error does not exceed 1.9%, which can confirm the accuracy of the developed model. A comprehensive analysis of the potential reduction in energy consumption with reduced freight wagon mass was also conducted. Using a freight wagon design with a reduced mass of 2.3% allows for a reduction in energy consumption by 8–89 kW·h, depending on the length of the section and the speed of movement.